2012
DOI: 10.1111/j.1744-7429.2012.00886.x
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Patterns of Species Richness and Composition of Solitary Wasps and Bees (Insecta: Hymenoptera) According to Land‐use

Abstract: Several species of arthropods inhabiting forest fragments interact with managed areas. The importance of such areas to biodiversity conservation, however, is not well established. Communities of solitary wasps and bees (Insecta: Hymenoptera) play a key role in agroecosystem functioning and they have been used in studies of biodiversity assessment in different land-use types. We aimed to assess patterns of species richness and composition of solitary wasps and bees over a 1-yr period in a gradient of decreasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 32 publications
4
18
0
Order By: Relevance
“…Several studies have found that richness and abundance of CNBW depends on various local and landscape factors, such as the proportion of seminatural habitat, edge density of surrounding landscape, vegetation structure, and microclimate (Steffan-Dewenter 2002, Holzschuh et al 2010, Batista Matos et al 2013). Using trap-nesting units, information on species richness, abundance, and interactions with nest associates (parasitoids, cleptoparasites, and nest scavengers) can be obtained simultaneously in different locations, and sampling effort can be standardized and replicated.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found that richness and abundance of CNBW depends on various local and landscape factors, such as the proportion of seminatural habitat, edge density of surrounding landscape, vegetation structure, and microclimate (Steffan-Dewenter 2002, Holzschuh et al 2010, Batista Matos et al 2013). Using trap-nesting units, information on species richness, abundance, and interactions with nest associates (parasitoids, cleptoparasites, and nest scavengers) can be obtained simultaneously in different locations, and sampling effort can be standardized and replicated.…”
Section: Introductionmentioning
confidence: 99%
“…During the recovery process many plant species become mature and start flowering and fruiting which attract insects (bees, wasps, butterflies, moths, beetles and flies) which is a major diet of avian species. Invertebrate communities of the tropical rain forest are highly diverse and their distribution and richness is associated with a diversity of vegetation structure and composition such as foliage, flowers, fruits, barks (Small and Pringle, 2010;Batista Matos et al, 2013;Peters et al, 2013). Silva and Brandao (2010) reported that invertebrate density strongly associated with vegetation structure and may vary at spatial scales of a few meters.…”
Section: Discussionmentioning
confidence: 99%
“…In heterogeneous landscapes consisting of multiple ecosystems types, the size and connectivity of (semi-)natural habitats increase trap-nesting bee and wasp diversity (e.g., Holzschuh et al, 2009;Steffan-Dewenter, 2003) and change species composition (e.g., Morato & Campos, 2000) according to hypotheses derived from island biogeography theory, but the strength of these effects may depend on the specific landscape context (Steckel et al, 2014). Similarly, land-use intensity in agricultural landscapes influences trap-nesting Hymenoptera composition and diversity (e.g., Matos, Sousa-Souto, Almeida, & Teodoro, 2013;Tylianakis, Klein, & Tscharntke, 2005), with less intensive and more varied cropping systems characterized by more bee and wasp species. However, in very intensively farmed areas, trap-nesting bees may depend on mass-flowering crops such as oilseed rape, which can increase bee abundance (e.g., Diekötter, Peter, Jauker, Wolters, & Jauker, 2014;Holzschuh, Dormann, Tscharntke, & Steffan-Dewenter, 2013).…”
Section: Landscape and Community Ecologymentioning
confidence: 99%
“…Landscape variables not only influence parasitoid diversity but also host-parasitoid interaction networks, which are usually simpler and less stable in more intensively used landscapes (Osorio et al, 2015;Tylianakis et al, 2007). Conversely, habitat restoration can increase the stability of host-parasitoid interactions in trap nests (Albrecht et al, 2007) (Matos et al, 2013;Stangler et al, 2015).…”
Section: Landscape and Community Ecologymentioning
confidence: 99%